Keabsahan Jual Beli Hak Atas Tanah Kepada Warga Negara Asing (WNA) - Meliza Meliza; Bintang Parashtheo (Journal of Law, Society, and Islamic Civilization, 2026)
This study seeks to examine the legal validity of transactions involving the sale and purchase of land rights by foreign nationals in Indonesia, as well as to identify the legal problems that frequently arise in practice. Indonesia’s national land law, especially Law Number 5 of 1960 concerning Basic Agrarian Principles, provides that ownership rights in the form of freehold title are reserved exclusively for Indonesian citizens, whereas foreign nationals may only obtain more limited forms of land rights, such as rights of use or rights acquired through certain legal entities in accordance with applicable laws and regulations. Nevertheless, in practice, attempts by foreign nationals to control land are still carried out through nominee arrangements, simulated transactions, and the misuse of legal entities. This research employs an empirical legal method with a socio-legal approach, viewing law as both a normative system and a social reality. The study was conducted in Bali Province, an area characterized by high levels of foreign investment and tourism activity. Primary data were obtained through in-depth interviews with officials of the National Land Agency (BPN), Notaries/Land Deed Officials (PPAT), and other relevant parties, as well as field observations. Secondary data were collected through library research consisting of statutory regulations, court decisions, books, and scientific journals. All data were analyzed using a descriptive qualitative method. The findings indicate that nominee arrangements and other forms of legal circumvention are contrary to the nationality principle in agrarian law and fail to satisfy the lawful cause requirement under contract law, rendering such transactions potentially null and void. In addition, weak administrative supervision, misuse of zoning regulations, and limited public understanding of land ownership restrictions for foreign nationals remain significant concerns. Therefore, stronger supervision, improved inter-agency coordination, and more effective legal education are necessary to ensure legal certainty and to protect national interests in the land sector.